2016
DOI: 10.1089/neu.2015.4064
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers to Spinal Cord Injury Clinical Trial Participation: Multi-National Perspective of People Living with Spinal Cord Injury

Abstract: These are exciting times for the translation of promising interventions for spinal cord injury (SCI) into testing with clinical trials. These interventions include acute surgical decompression, neuroprotection, neural repair, cell replacement, activity-based rehabilitation, and medical devices, including devices requiring surgical implantation. By nature, clinical trials can have strict inclusion and exclusion criteria, which narrow down the pool of potential participants. Meeting enrollment numbers for proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 12 publications
1
21
1
Order By: Relevance
“…The consumer survey included 802 participants; the number one facilitator for participating in clinical research was the possibility of improving functionality and the number one barrier was the possibility of a decline in functionality. 24 While these results may have been expected, the unexpected facilitators and barriers that emerged from the survey include the possibility to learn more about their general health/SCI and potential out-of-pocket expenses, respectively. 24 The main goal of performing these surveys was to determine how SCI consumers, researchers, and organizations can work together to best support, design and conduct international SCI clinical research collaborations.…”
Section: Introductionmentioning
confidence: 91%
“…The consumer survey included 802 participants; the number one facilitator for participating in clinical research was the possibility of improving functionality and the number one barrier was the possibility of a decline in functionality. 24 While these results may have been expected, the unexpected facilitators and barriers that emerged from the survey include the possibility to learn more about their general health/SCI and potential out-of-pocket expenses, respectively. 24 The main goal of performing these surveys was to determine how SCI consumers, researchers, and organizations can work together to best support, design and conduct international SCI clinical research collaborations.…”
Section: Introductionmentioning
confidence: 91%
“…The loss of arm and hand function therefore leads to a severe loss of independence. This sense of loss is reflected in studies of people with spinal cord injury who report that restoration of arm and hand function is a top priority 1 – 3 . For injuries like spinal cord injuries and amputation, assistive technology is required to replace the functions previously performed by the arm and hand.…”
Section: Introductionmentioning
confidence: 99%
“…Patient adherence to the intervention is described at discharge by the patient, who will document participation in targeted education elements using a checklist. However, a 2016 study found that the most important factor facilitating participation in clinical studies was the possibility of learning more about SCI and health, which is a clear potential in the intervention study 73. A review by Van Wyk et al emphasises that patient education is an important part of the interdisciplinary rehabilitation of people with SCI and recommend an individualised approach and the use of different settings in which the patient can receive the education 29…”
Section: Discussionmentioning
confidence: 99%